PENGARUH NORMA SUBJEKTIF, KEWAJIBAN MORAL DAN PEMAHAMAN PERATURAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Yolanda Pratiwi; Enan Trivansyah Sastri (Jurnal Nusa Akuntansi, 2025)
This study aims to determine and test the influence of Subjective Norms, Moral Obligations, and Understanding of Tax Regulations both partially and together (simultaneously) on taxpayer compliance registered at the Bogor Pratama Tax Service Office. This study uses a quantitative method with a sample of 100 respondents. Respondents in this study were taxpayers registered at the Bogor Pratama Tax Service Office. The data analysis technique used to answer the hypothesis is multiple linear regression analysis. The results of the research that has been conducted state that subjective norms have a positive effect on taxpayer compliance. Moral obligations have a positive effect on taxpayer compliance. Understanding of tax regulations has a positive effect on taxpayer compliance. Subjective norms, moral obligations, and understanding of tax regulations together affect taxpayer compliance.